Mineralogical and geochemical records of seafloor cold seepage history in the northern Okinawa Trough, East China Sea. (January 2020) - Cao, Hong; Sun, Zhilei; Wu, Nengyou; Liu, Weiliang; Liu, Changling; Jiang, Zike; Geng, Wei; Zhang, Xilin; Wang, Libo; Zhai, Bin; Jiang, Xuejun; Liu, Liping; et al.
Abstract: Cold seep carbonate represents a faithful record of the ancient methane seepage and provides a nonnegligible contribution to the global carbon reservoir. On the western slope of the Northern Okinawa Trough (NOT), a recent seafloor visualized survey has discovered widespread crust of cold seep carbonate. Here we study mineralogy and geochemistry of these authigenic carbonate to investigate source origin and reconstruct its growth history. Mineralogically, the carbonate crusts are mainly composed of micritic aragonite, with botryoidal aragonite, framboidal pyrite, and microcrystalline authigenic gypsum. Petrographic characteristic unambiguously indicates that this carbonate precipitates in relatively open systems due to a considerable rate of sulfate-dependent anaerobic oxidation of methane (AOM). Regarding geochemistry, strongly 13 C-depleted carbon isotope values (as low as −56.1‰, V-PDB) demonstrate that the carbon in the carbonate crusts is mainly derived from biogenic methane coupled with AOM. In contrast, the δ 18 O enrichment (up to +2.7‰, V-PDB) suggests that the fluid flow from which carbonate precipitated is sourced from dissociation of underlying natural gas hydrates. The U–Th ages of authigenic carbonates fall in the timescale of 22.8–55.7 ka BP, consistent with the period of sea-level lowstand in the late Pleistocene. Overall, several lines of evidence of this study indicate that extensive methane was released by gas hydrate decomposition during sea level fall, consequently resulting in the precipitations of carbonate crust in the NOT. Furthermore, the obviously episodic methane seepages led to the constant accretion from the interior to the exterior within the preformed crust, ultimately inducing the carbonate blocks, slabs and crusts to be exposed on the seafloor. The existence of large-scale carbonate crusts represents a good trapper of the later released carbon especially the isotopically light methane from the deep. Highlights: Aragonite is the dominated mineral phase in carbonate crust of Okinawa Trough. Carbonate is sourced from gas hydrate and carbon mainly from biogenic methane. U–Th age of carbonate crust is within the periods of sea-level lowstand.